The influence of the vulnerability of sectors on their survival and probability of insolvency: The case of small and medium entities in Spain - Antonio Somoza (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2021)
This paper looks at a sample of small and medium entities in Spain and analyzesthe effect of the vulnerability of sectors to insolvency on their survival and the probability that they will go bankrupt. We collected data from solvent and insolvent firms in Spain over the period 2012-2016, and grouped them according to the percentage of insolvencies by sector (highest, lowest, and a reference group). The results show that no differences in the endurance of the firms emerge among the groups, while some variables appear to be relevant when the logit analysis is applied. Survival depends on liquidity and size in all industries, but profitability and turnover are also essential for the group with the highest levels of insolvency. The probability of bankruptcy is mainly explained by turnover and short-term solvency. Size and turnover have negative effects on bankruptcy. Age is also a common factor, but with a different interpretation for each technique. The main contribution of this paper is the analysis of insolvency in the two dimensions of survival and probability according to the sectorial insolvency rate.
Keywords: G33; M41; M21; 330; insolvency; bankrutpcy; survival; logit; Spain